If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 + 10 = m + -5 Combine like terms: -24 + 10 = -14 -14 = m + -5 Reorder the terms: -14 = -5 + m Solving -14 = -5 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -14 + -1m = -5 + m + -1m Combine like terms: m + -1m = 0 -14 + -1m = -5 + 0 -14 + -1m = -5 Add '14' to each side of the equation. -14 + 14 + -1m = -5 + 14 Combine like terms: -14 + 14 = 0 0 + -1m = -5 + 14 -1m = -5 + 14 Combine like terms: -5 + 14 = 9 -1m = 9 Divide each side by '-1'. m = -9 Simplifying m = -9
| 7x-35=-2(-8x+4) | | 15=5-n | | 17=-5 | | 8x+1=-16 | | -6x+4(x-4)=-14 | | 72c=8 | | 26-(x-11)=-5(x+7) | | 5m+2m-5= | | x/-13=-40 | | w=2x^2-yz | | y=0.5x+1.5 | | 14*30+d=-196 | | (4+1)+2= | | 8y+2=21 | | 14+30+d=-196 | | 3=x(9-2x)(6-2x) | | 20=s-5 | | 7x+9+3x+1=8x-5 | | 8x-11=-5 | | 4/5n-7=17 | | 4log(x)-log(x^4)= | | 2(3x-2)=10x-13-7x | | 2x^3+3x^2-8x-4=0 | | 2n+-3n+-14=0 | | 4m-9=11 | | 9x-4=4x+27 | | 2(-5x-7)=16 | | 2[-(2+13)+11]=2(x+2) | | -7(2x-3)=28 | | .6-0.25f=f-3 | | 4ln(x)-ln(x^4)= | | Y=.5(3)+1 |